О точном методе факторизации составных чисел - Семотюк, М.В. (Комп’ютерні засоби, мережі та системи, 2011)
Предложен метод факторизации составных чисел, позволяющий за конечное число итераций, равное log2N/2, найти сомножители, решать диофантовы уравнения, проверять простоту чисел. Запропоновано метод факторизації складних чисел, що дозволяє за скінчене число ітерацій, рівному log2N/2, знайти співмножники, вирішувати діофантові рівняння, перевіряти простоту чисел. We propose a method of factoring composite numbers on the basis of digit by digit makes it lyayuschy finite number of steps (iterations) equal to log2 N / 2 to find the factors due to number-theoretic concepts of number systems. The method allows reshat Diophantine equations, as well as get an accurate test for primality.